2021
DOI: 10.1039/d0ra08353d
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun collagen core/poly-l-lactic acid shell nanofibers for prolonged release of hydrophilic drug

Abstract: A hydrophilic drug was encapsulated in nanofibers with hydrophobic shell using core–shell electrospinning. Drug–polymer miscibility affected the crystallinity of drug-loaded nanofibers. Our results propose a way to prolong the release of hydrophilic drugs from nanofibers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 60 publications
0
21
0
Order By: Relevance
“… Microstructure of PLLA-based hybrid scaffold in combination with natural polymers, synthetic polymers or inorganic biomaterials. Reprinted with permission from RSC [ 135 ] and MDPI [ 136 , 137 ]. …”
Section: Figurementioning
confidence: 99%
“… Microstructure of PLLA-based hybrid scaffold in combination with natural polymers, synthetic polymers or inorganic biomaterials. Reprinted with permission from RSC [ 135 ] and MDPI [ 136 , 137 ]. …”
Section: Figurementioning
confidence: 99%
“…On the other hand, core-shell nanofibers provided a controllable long-term release, which could be induced by diffusion and slow degradation of the shell, being the complete release achieved after 192 h. Figure 9 shows the proposed drug release mechanism from monolithic and core-shell nanofibers. [59] Alishahi et al showed that the core-shell structures were able to reduce the initial burst release and prolong the release for 9 h, whereas almost all the loaded drug was released after 5 h when using single blended nanofibers. [140] Another research work also demonstrated the ability of core-shell to decrease the initial burst release obtained with blended nanofibers.…”
Section: Drug Release Profiles From Electrospun Fibersmentioning
confidence: 99%
“…Electrospinning is one of the feasible techniques for the fabrication of topographic patterns. The architecture of electrospun nanofibers is similar to the collagen structure in natural ECM that supports cells with mechanical properties and chemical signals. Nanofibers with a controlled orientation are used to guide cell migration and interdict cell spreading . They can also be used to mimic the aligned topographical features of the white matter tract in vivo microenvironment, because the white matter tracts with highly oriented structures serve as migration routes for GBM cells.…”
Section: Introductionmentioning
confidence: 99%